Analysis of the Clinical Characteristics of Spontaneous Bile Duct Perforation in Children - Yan, Xueqiang; Zheng, Nannan; Jia, Jinfu; Kuang, Houfang; Lei, Haiyan; Bian, Hongqiang; Qin, Xinke; Sun, Xuan; Duan, Xufei; Zhan, Jianghua (Frontiers in Pediatrics, 2022)
Objective This study aimed to explore the etiology, clinical features, diagnosis, and treatment of spontaneous bile duct perforation (SBDP) in children. Methods The clinical data of children with SBDP who were admitted to Wuhan Children's Hospital between January 2014 and January 2020 were retrospectively analyzed. Results In all, 28 cases of children with SBDP (male, 28.6%; female, 71.4%; male-to-female ratio, 1:2.5; average age, 2.15 years) were analyzed. The most common symptoms were fever (85.7%), nausea and vomiting (78.6%), and abdominal distension (67.9%). Among the 28 patients, 26 (92.9%) had elevated hypersensitive C-reactive protein, 24 (85.7%) had an increased neutrophil percentage, and 22 (78.6%) had raised peripheral blood leukocyte counts. Moreover, 19 patients (67.9%) showed increased serum total bilirubin levels, and 5 (17.9%) showed an elevated conjugated bilirubin level. Abdominal CT examination revealed that the gallbladder wall of patients was thickened with edema, accompanied by gallbladder stenosis and gallbladder mucosa enhancement; furthermore, ascites was found in the abdominal cavity and lesser omental bursa. Twenty-two patients underwent abdominal paracentesis, and 20 (90.9%) of them were exposed to bile-based ascites. Among the 28 patients, four recovered with conservative treatment, whereas the others (85.7%) were surgically treated. Of the twenty-four patients undergoing surgery, the perforation site was found at the union of the hepatic and cystic ducts in 12 patients (50%), no perforation site was observed in 9 patients (37.5%), and a common hepatic duct was observed in 3 patients (12.5%). All 24 patients underwent stage I surgery, and temporary biliary drainage was performed because of severe abdominal inflammation. Cholangiography and enhanced CT revealed an abnormal location of the pancreatic duct joining the bile duct in 64.3% patients. Following surgery, 15 patients underwent hepaticojejunostomy. Subsequently, 3-month to 6-year follow-up (median, 30 months) indicated that the patients recovered well with no serious complications. Conclusion SBDP in children may be associated with pancreaticobiliary malunion (PBM) and congenital weakness of the bile duct wall. However, the clinical manifestations of this condition lack specificity; this limitation can be assisted through diagnosis via abdominal CT and by performing abdominal paracentesis. Once SBDP diagnosis is confirmed, the patient should follow the principles of individualized treatment.